Development of Student Worksheets Based on Guided Discovery Learning Assisted by Tracker Video Analysis on Mechanical Energy Conservation Material - Luthfi Rahman; Aripin Aripin; Yanti Sofi Makiyah (Jurnal Ilmiah Pendidikan Fisika, 2024)
Student worksheets based on guided discovery learning assisted by a tracker video analysis on mechanical energy conservation materials were developed to provide experience in learning physics on conservation material mechanical energy. This research aims to produce a product in the form of the student worksheets based on guided discovery assisted by tracker video analysis. Studying this is research and development (R&D), using the ADDIE model, which consists of 5 stages: analysis, design, development, and implementation. This study uses quantitative data and qualitative data. Quantitative data results from the validation sheet and questionnaire responses of students and teachers. Then, qualitative data will be collected as suggestions, comments, and criticism from the validator regarding the development of the student worksheets. Data collection techniques using interviews and observations. The instrument used is a validation sheet for three validators: media, material, and language experts. This research was held at the Riyaluul Ulum High School. The research subjects were physics teachers and students of class X MIPA. The sample consisted of 130 students who were taken using simple random sampling and two teachers. Data analysis technique using descriptive statistics to determine validity and practicality. The results showed that the average value of media validation was 83% and categorized as very valid, material validation was 82% and categorized as very valid and language validation was 77% and categorized as valid. The results of the practicality assessment by students is 80% with the category of practical, and by the teacher is 86% very practical. The results of this study state that it can be used and implemented in the learning process.